Subcritical water extraction of low methoxyl pectin from pomelo ( Citrus grandis (L.) Osbeck) peels - Liew, Shan Qin; Teoh, Wen Hui; Tan, Chee Keong; Yusoff, Rozita; Ngoh, Gek Cheng (Elsevier, 2018)
Low methoxyl (LM) pectin was extracted from pomelo peels using subcritical water in a dynamic mode. The effects of pressure and temperature were analyzed through a face-centred central composite design. Extraction yield and the rate of extraction were found to be predominantly influenced by temperature. Optimization of the subcritical water extraction (SWE) yielded an optimized operating condition of 120 °C and 30 bar with a predicted pectin yield of 18.8%. The corresponding experimental yield was 19.6%, which is in close agreement with the predicted data. The pectin obtained from the optimized condition was further analyzed for its physicochemical properties. The kinetics of the SWE was also evaluated whereby the one-site kinetic desorption model was found to be in good agreement with experimental data (R2 > 0.94).